Impacts of forced marriages in Cambodia under the Pol Pot regime - Katsuo Kogure (Osaka University, Institute of Social and Economic Research (ISER), 2011)
This paper investigates effects of forced marriages in the Pol Pot regime on educational investments for their children. Specifically, we focus on the difference in educational investments between the couples who faced different social environments under the Pol Pot regime. Using the complete set of retrospective census microdata, we estimate the average treatment effects on the treated with inverse probability weighting estimation. Our estimation results suggest that forced marriages had negative impacts on child education. In particular, a harsher social environment had larger negative impacts on child education.
Additional information: The 13th ISER-Moriguchi Prize (2010) Awarded Paper.
Keywords: N45; O43; P36; 330; child education; forced marriage; the Pol Pot regime; Ehe; Kinder; Bildungsniveau; Familienplanung; Kommunismus; Geschichte; Kambodscha